Early records of Neomonachus tropicalis (Gray, 1850) in Venezuela (Mammalia, Pinnipedia: Phocidae): Registros antiguos de Neomonachus tropicalis (Gray, 1850) en Venezuela (Mammalia, Pinnipedia: Phocidae) - Viloria, Ángel L.; Sánchez-Criollo, Leonardo; Briceño, Yurasi A. (Anartia, 2025)
The Jamaican seal or Caribbean monk seal, Neomonachus tropicalis (Gray, 1850), a pinniped mammal of the American Tropical Atlantic, has been declared extinct several times (Timm et al. 1997, Adam & García 2003, McClenachan & Cooper 2008, Scheel et al. 2014, Jørgensen 2021, Luna-Pérez & Cuevas-Cardona 2022, CITES 2024). It was described by Gray (1850: 28-29) based on an incomplete skin from Jamaica, when only small groups survived in some isolated points of its former distribution area (McClenachan & Cooper 2008). Its unfortunate disappearance is attributed, with good historical evidence, to indiscriminate hunting and the greed of collectors (McClenachan & Cooper 2008, Jørgensen 2021). The species was also considered extinct in the Venezuelan Caribbean (Rodríguez & Rojas-Suárez 2008: 362-363), but a few years later its name was not even included in the Red Book of Venezuelan fauna (Rodríguez et al. 2015). In fact, until now, no authentic report of the presence of N. tropicalis in Venezuela had ever been recognized. Past records and archaeological findings demonstrate that this seal was present in the Netherlands Antilles near the Venezuelan coast (van Grol 1934, Harviser 1987, 1994, van Bree 1994, Debrot 2000). Based on toponymic information, Adam & García (2003: 317) presumed its possible historical occurrence in two Venezuelan localities, Cerro El Lobo (Carabobo state, highly improbable) and Isla Lobos or Islote Los Lobos (Sucre state, see Balda 1963). This information was echoed by McClenachan & Cooper (2008: 1355, fig. 3). In 2009, one of the authors (ALV) visited the towns of Guayacán, Chacopata, and Isla Caribe, not far from Isla Lobos, where some fishermen did indeed recognize that the name of the islet derives from the ancient presence of “lobos marinos” on the site. None of them attested to having encountered this animal, only hearing references from their ancestors.